2013
DOI: 10.1002/cphc.201300610
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of the One‐ and Two‐Dimensional Infrared Spectra of a Proton‐Transfer Mode in a Hydrogen‐Bonded Complex Dissolved in a Polar Nanocluster

Abstract: The signatures of nanosolvation on the one- and two-dimensional (1D and 2D) IR spectra of a proton-transfer mode in a hydrogen-bonded complex dissolved in polar solvent molecule nanoclusters of varying size are elucidated by using mixed quantum-classical molecular dynamics simulations. For this particular system, increasing the number of solvent molecules successively from N=7 to N=9 initiates the transition of the system from a cluster state to a bulk-like state. Both the 1D and 2D IR spectra reflect this tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…In order to elucidate the signatures of nanoconfinement on ground-state proton-transfer reactions in nonlinear vibrational spectra, we compute both the one-dimensional IR (1D-IR) and IR pump–probe spectra of a proton-transfer mode in a model H-bonded phenol–amine complex dissolved in pools of methyl chloride molecules confined in various nanosized spherical hydrophobic cavities. Calculations of the proton-transfer rate constant have been carried out for this complex in bulk methyl chloride and in small unconfined methyl chloride clusters. , In addition, the signatures of solvation and proton-transfer dynamics in these systems have been investigated in simulated 1D-IR, 2D-IR, and IR pump–probe spectra. It should be noted that a similar model has been studied previously by Thompson and co-workers, ,, but, in contrast to our study, their hydrogen-bonding potential governing the proton-transfer dynamics was different and the O–N bridge length in the complex was constrained. In ref , Monte Carlo simulations were used to investigate the distribution of the complex’s position in the cavity and it was found that the proton-transfer reaction involves diffusion of the complex from the cavity wall to the interior of the cavity and vice versa.…”
Section: Introductionmentioning
confidence: 67%
“…In order to elucidate the signatures of nanoconfinement on ground-state proton-transfer reactions in nonlinear vibrational spectra, we compute both the one-dimensional IR (1D-IR) and IR pump–probe spectra of a proton-transfer mode in a model H-bonded phenol–amine complex dissolved in pools of methyl chloride molecules confined in various nanosized spherical hydrophobic cavities. Calculations of the proton-transfer rate constant have been carried out for this complex in bulk methyl chloride and in small unconfined methyl chloride clusters. , In addition, the signatures of solvation and proton-transfer dynamics in these systems have been investigated in simulated 1D-IR, 2D-IR, and IR pump–probe spectra. It should be noted that a similar model has been studied previously by Thompson and co-workers, ,, but, in contrast to our study, their hydrogen-bonding potential governing the proton-transfer dynamics was different and the O–N bridge length in the complex was constrained. In ref , Monte Carlo simulations were used to investigate the distribution of the complex’s position in the cavity and it was found that the proton-transfer reaction involves diffusion of the complex from the cavity wall to the interior of the cavity and vice versa.…”
Section: Introductionmentioning
confidence: 67%
“…These results are qualitatively compared to the results of adiabatic dynamics simulations in Refs [73,74], which are known to give a realistic picture of the dynamics.…”
Section: Complex and Solvent Propertiesmentioning
confidence: 85%
“…It should be noted that the PT kinetics [73] and 1D-IR/2D-IR spectroscopy [74] of this model were previously investigated. Within our mixed quantum -classical approach, the proton constitutes the quantum subsystem and the remaining atoms constitute the classical environment.…”
Section: Modelmentioning
confidence: 98%
“…While Geva et al 37−39 and Hanna 40,41 have applied MQCLE to calculate vibrational spectra in MQC environment, Hanna 42,43 calculated Optical response function to probe electron transfer dynamics using the basis mapping technique developed by Nassimi and Kapral. 44 However, the path to the end results, approach, purpose, rigor, applications, and results differ from those reported by Toutounji.…”
Section: Introductionmentioning
confidence: 99%
“…The response function approach has been widely utilized in calculating spectroscopic signals to probe systems of interest. , For example, Staib and Borgis employed quantum-classical dynamics to compute IR spectra of OH stretch mode spectra of hydrogen-bonded methanol complexes dissolved in carbon tetrachloride are computed; however, MQCLE was never used in their simulation and no electronic spectra were reported. While Geva et al and Hanna , have applied MQCLE to calculate vibrational spectra in MQC environment, Hanna , calculated Optical response function to probe electron transfer dynamics using the basis mapping technique developed by Nassimi and Kapral . However, the path to the end results, approach, purpose, rigor, applications, and results differ from those reported by Toutounji. , The optical response function developed by Hanna , to probe electron transfer dynamics seems to neglect frequency change (excited state vibrational force constant change) and anharmonicity upon electronic excitation, and they do not seem to offer in-depth spectroscopic analysis, especially with respect to electronic dephasing, electron–phonon coupling, shape, and symmetry of spectral profiles, all of which mark differences compared to MQCD-based report reviewed herein.…”
Section: Introductionmentioning
confidence: 99%